Modelling innovation performance of Turkish construction companies - Oral, Kutluhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
The construction industry has always been high importance of the national economy. Due to increasing pressures from clients to improve quality, reduce costs and speed up construction processes, innovation can be a key source of competitive advantage for construction companies. On the other hand, construction industry has also long been criticised for exhibiting low rates of innovative activity and its unwillingness to innovate. Construction is a project based and fragmented industry, the patterns of construction innovation are different from the other industries and much of the innovation co-developed at the project level and remains hidden. An appropriate innovation performance measurement system is needed to better understand of the actual level of innovation in construction. The major aim of this research is to develop a comprehensive model which aims at assessing the innovation performance in construction at the project level. In order to achieve this, an extensive literature survey was conducted to find the most appropriate components of innovation including the drivers, enablers, barriers, inputs, benefits and impacts. Then, the interrelationships between those components were identified and the proposed model was tested based on data collected from the Turkish construction companies. The validity of the model was tested by statistical analyses using structural equation modelling (SEM). Findings of the study suggest that drivers and enablers have a highly positive effect on inputs. In addition, inputs have positive affect on benefits and impacts. It is interesting that since the drivers and enablers have a high positive impact on the inputs, the effect of the barriers has become negligible. Proposal of such a framework has considerable contributions to measure the innovation capabilities of companies in Turkish construction industry. This model aims to help companies to be aware of the innovation performance of their company and decide on long-term strategies accordingly.
Keywords: Construction industry -- Turkey.; Construction industry -- Technological innovations.